A case study of the development of occupational therapy at St. Patrick’s Hospital Dublin, 1935-1969 - Bríd D. Dunne; Katie Robinson; Judith Pettigrew (Irish Journal of Occupational Therapy, 2017)
Purpose - This paper aims to examine the relationship between psychiatry and occupational therapy in Ireland through a case study of the development of the occupational therapy department in St. Patrick’s Hospital, Dublin, from 1935 to 1969. Patronage by psychiatrists was an important factor in the professionalisation of occupational therapy internationally. Design/methodology/approach - Documentary sources and oral history interviews were analysed to conduct an instrumental case study of occupational therapy at St. Patrick’s Hospital from 1935 to 1969. Findings - The research identified key individuals associated with the development of occupational therapy at St. Patrick’s Hospital, including psychiatrist Norman Moore, occupational therapy worker Olga Gale, occupational therapist Margaret Sinclair, and social therapist Irene Violet Grey. Occupational therapy was considered by the hospital authorities to be “an important part in the treatment of all types of psychiatric illness” (Board Meeting Minutes, 1956). It aimed to develop patient’s self-esteem and facilitate social participation. To achieve these objectives, patients engaged in activities such as dances, arts and crafts, and social activities. Originality/value - This study has highlighted the contributions of key individuals, identified the links between occupational therapy and psychiatry, and provided an insight into the development of the profession in Ireland prior to the establishment of occupational therapy education in 1963. Occupational therapy practice at St. Patrick’s Hospital from 1935 to 1969 was congruent with the prevailing philosophy of occupational therapy internationally, which involved treatment through activities to enhance participation in society.